Active surveillance for patients with very low‐risk thyroid cancer. Issue 1 (7th February 2020) - Lohia, Shivangi; Hanson, Martin; Tuttle, R. Michael; Morris, Luc G. T.
Abstract: Over the past 30 years in the United States, increasing identification of small thyroid nodules has led to a dramatic rise in the detection of small thyroid cancers, many of which are unlikely to progress to overt clinical disease. Because autopsy studies reveal that up to 30% of people harbor clinically occult thyroid cancers, the growing use of diagnostic technologies has identified an increasing number of small, clinically low risk papillary thyroid cancers (PTCs). In recent years, clinical practice has evolved to de‐intensify the treatment for PTCs, with fewer total thyroidectomy and nodal dissection procedures being performed, in favor of more limited operations. In addition, vigilant observation of selected low risk cancers has demonstrated outcomes comparable to those patients who undergo immediate surgical intervention. Active surveillance has emerged as a new option within the treatment algorithm of PTCs. There is now robust data from cancer centers in Japan and Korea which have reported excellent oncologic outcomes among patients undergoing active surveillance for PTC, as well as more recent, similar data from the United States. American Thyroid Association guidelines now include the option of active surveillance for appropriately selected patients with low‐risk PTC. With active surveillance now one option within the standard of care for patients with certain thyroid cancers, surgeons have become critical to facilitating shared decision‐making for patients facing this diagnosis.